2002
DOI: 10.1152/ajpheart.00766.2001
|View full text |Cite
|
Sign up to set email alerts
|

Impaired collateral development in mature rats

Abstract: The effect of maturation on collateral development of resistance arteries was investigated. Three to four sequential mesenteric arteries were ligated to create collateral pathways in anesthetized young (ϳ200 g) and mature (ϳ600 g) rats. Blood flow was similarly elevated in collaterals of young and mature animals. In vivo inner arterial diameter was increased only within young collaterals (33 Ϯ 7%, P Ͻ 0.001). Increases in number of intimal nuclei (57 Ϯ 10% vs. 52 Ϯ 14%) and cross-sectional medial area (33 Ϯ 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
41
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 46 publications
12
41
0
Order By: Relevance
“…Superoxides and NO are also able to activate HSPs production 87 and both are produced by endothelial cells in response to shear stress 47 . Enolase, which has properties similar to those of HSPs, is also increased in mesenteric resistance arteries submitted to high flow in young and mature rats 81 . In young rats diameter and medial mass increased whereas in mature rats medial hypertrophy occurred without increase in diameter 81 .…”
Section: -Role Of Structure Proteins In the Adaptation Of The Microcmentioning
confidence: 89%
See 3 more Smart Citations
“…Superoxides and NO are also able to activate HSPs production 87 and both are produced by endothelial cells in response to shear stress 47 . Enolase, which has properties similar to those of HSPs, is also increased in mesenteric resistance arteries submitted to high flow in young and mature rats 81 . In young rats diameter and medial mass increased whereas in mature rats medial hypertrophy occurred without increase in diameter 81 .…”
Section: -Role Of Structure Proteins In the Adaptation Of The Microcmentioning
confidence: 89%
“…Interestingly, in mature rats (8-10 month-old) vimentin content was lower than in young animals and no diameter expansion occurred after a chronicle increase in blood flow 81 . In high flow resistance arteries several heat shock proteins (HSP) expression level increased as well, which is a characteristic of a response to a stress 81 . HSPs may be involved in the stabilization of cytoskeletal element after diameter expansion 82 .…”
Section: -Role Of Structure Proteins In the Adaptation Of The Microcmentioning
confidence: 93%
See 2 more Smart Citations
“…These changes may contribute to chronically elevated levels of retrograde shear stress with older age,24, 25 and may also impact upon the ability of the vasculature to respond to changes in retrograde shear. Interestingly, previous studies in animals reported distinct adaptations to shear stress between young and older individuals 26, 27, 28, 29. However, no previous study has explored whether prolonged exposure to elevated retrograde shear leads to distinct adaptations in brachial artery vasomotor function between healthy young and older humans.…”
Section: Introductionmentioning
confidence: 98%